HUBUNGAN PERSEPSI CITRA TUBUH DAN GEJALA DEPRESI DENGAN KEJADIAN GANGGUAN MAKAN PADA REMAJA OBESITAS - Adji, Seno Bayu; Fitrikasari, Alifiati; Julianti, Hari Peni (Universitas Diponegoro, 2019)
Background: Adolescence is a stage where a person begins to pay attention to body shape and crave an ideal body. This attention to self affects the perception of body image. Obesity can cause conflict within itself and can cause depression.Those who feel dissatisfied with their appearance try to get an ideal body shape including eating unhealthy behavior so that it becomes an eating disorder.Aim : To analyze the relationship between body image perception and depressive symptoms with the incidence of eating disorders in obese adolescents.Method : An observational study with a cross sectional design on 25 students of the Medical Faculty of Diponegoro University using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) test, the Beck Depression Inventory - II (BDI-II) and Eating Attitude Test-40 (EAT-40).Results : Body image perception, Negative evaluation appearance 2 persons, normal 23 persons. Negative appearance orientation 12 persons, normal 13 persons. Negative body area satisfaction 11 persons, normal 13 persons, positive 1 person. Normal overweight preoccupation 20 persons, positive 3 persons, negative 2 persons. Normal self-classified weight 22 persons, positive 3 persons.Depressive symptoms, 15 persons showed no symptoms of depression, 8 persons had mild depressive symptoms, 1 person had moderate depressive symptoms and 1 person had severe depressive symptoms.Eating disorders, 3 persons experienced eating disorders and 22 persons did not experience eating disorders.Evaluation of appearance has a significant effect on the incidence of eating disorders. p <0.05, OR = 23, and CI95% = 3.382 - 156,396.Conclusion: Appearance evaluation gives 23 times the influence of eating disorders.Keywords: adolescent obesity, body image, depression, eating disorders.